Human retroviruses in Amerindians of Colombia - high prevalence of human T-cell lymphotropic virus Type-II infection among the Tunebo Indians (2022)
eng: The coexistence of infection with human T lymphotropic virus types I and II (HTLV-I and HTLV-II) has been demonstrated recently among the Wayuu Indians from the Guajira region of Colombia. To ascertain if other Indian groups in Colombia are similarly infected, we tested 1,250 sera, collected between 1990 and 1992 from 18 culturally distinct Amerindian tribes living in widely separated regions, for IgG antibodies against HTLV-I/II using enzyme-linked immunosorbent assay (ELISA) and Western blot. Sera were also tested for antibodies against human immunodeficiency virus types 1 and 2 (HIV-1 and HIV-2) to investigate the overall burden of retrovirus infection in these semi-isolated indigenous groups. A total of 33 of the 1,250 samples were repeatedly reactive to HTLV-I/II antigens by ELISA, and of these, three sera from Waunana/Noanama Indians from the Choco area and two sera from Tunebo Indians from the Santander region were found to be infected with HTLV-I and HTLV-II, respectively, as verified by Western blot and differential ELISA. Thus, despite the small sample size, the overall seroprevalences for HTLV-I and HTLV-II infection among the Waunana/Noanama and Tunebo Indians were 2.1% and 5.0%, respectively. In contrast, none of the 29 Indians who exhibited reactivity to HIV-1/2 by ELISA were seropositive by Western blot. This study adds the Tunebo to the expanding list of Amerindian groups with high prevalences of HTLV-II infection. Further intensive investigations of such indigenous populations will clarify the natural history and disease potential of HTLV-II infection.